Jurnalisme Investigasi Majalah Tempo (Analisis Wacana Jurnalisme Edisi Main Upeti Izin Tambang) - Aditia .; Ahmad Harun Yahya; Lilis Sukmawati (CV. ITTC INDONESIA, 2026)
This study aims to analyze the discourse strategies of investigative journalism in Tempo magazine’s edition “Main Upeti Izin Tambang” using Teun A. van Dijk’s Critical Discourse Analysis approach. The focus of the study is on how macrostructure, superstructure, and microstructure within news texts construct meanings related to the abuse of authority in mining permit issuance by state officials. This research employs a descriptive qualitative approach with critical discourse analysis as the method. Data were collected through documentation of Tempo news texts, observation, and a review of relevant literature. The findings indicate that Tempo represents corruption in mining permit issuance as a serious public issue by emphasizing transparency, accountability, and social justice. At the macro level, the discourse of “main upeti” is constructed as a form of power deviation that harms the state and society. At the superstructural level, the narrative is systematically organized through patterns of case introduction, factual disclosure, and the reinforcement of the urgency of corruption eradication. Meanwhile, at the microstructural level, the selection of diction, language style, and rhetorical strategies is used to strengthen criticism of bureaucracy and to build public awareness. This study concludes that Tempo’s investigative journalism functions not only as a medium for information dissemination but also as an ideologically charged social construction that plays a strategic role in shaping public opinion, exercising social control, and challenging the normalization of corrupt practices in the mining sector.